Diabetic Mastopathy: An Uncommon Complication of Diabetes Mellitus - R. X. Kirby; D. I. Mitchell; N. P. Williams; D. A. Cornwall; S. O. Cawich (Case Reports in Surgery)
Introduction. Whilst most consequences of diabetes mellitus are well recognized, breast-related complications remain obscure. The term diabetic mastopathy (DMP) attempts to describe the breast-related consequences of diabetes. Methods. We report the clinicopathologic findings in a patient with DMP and review the literature on this uncommon entity. Results. A 33-year-old woman with type 1 diabetes had excision biopsy of a 2 cm breast lump. Histopathologic evaluation revealed classic features of DMP: parenchymal fibrosis; keloid-like hyalinization of interlobular stroma; adipose tissue entrapment; lobular compression; dense chronic inflammatory cell infiltration; and lymphoid follicle formation. Conclusion. Clinicians should be aware of DMP as a differential for breast disease in women with uncontrolled diabetes.